Peripheral blood stem cell transplantation vs. bone marrow transplantation for aplastic anemia: a systematic review and meta-analysis - Zhang, Zhao; Zhou, Xianghui; Cheng, Zhipeng; Hu, Yu (Frontiers in Medicine, 2023)
Background: Hematopoietic stem cell transplantation (HSCT) is an effective treatment for aplastic anemia. Recently, peripheral blood stem cell transplantation (PBSCT) has gradually replaced traditional bone marrow transplantation (BMT). However, which graft source has a better therapeutic effect and prognosis for aplastic anemia (AA) remains unclear. Therefore, we conducted this systematic review and meta-analysis.We systematically searched PubMed, EMBASE, and the Cochrane Library without language limitations for studies using PBSCT or BMT for AA. Data were analyzed using the Open Meta-Analyst.We identified 17 of 18749 studies, including seven comparative reports and nine single-arm reports, with a total of 3516 patients receiving HSCT (1328 and 2188 patients received PBSCT and BMT, respectively). The outcomes of the comparative studies showed similar 5-year overall survival (OS) (relative risk [RR]=0.867; 95% confidence interval [CI], 0.747-1.006), similar transplantrelated mortality (RR=1.300; 95%CI, 0.790-2.138), graft failure rate (RR=0.972; 95%CI, 0.689-1.372) between the PBSCT group and the BMT group, while the PBSCT group had a significantly higher incidence of chronic graft-versus-host disease (GVHD) (RR=1.796; 95% CI, 1.571-2.053) and a higher incidence of grade IV acute GVHD (RR=1.560; 95% CI, 1.341-1.816) compared to the BMT group. The outcomes of single-arm reports showed similar 3-year OS and incidences of chronic GVHD, acute Ⅱ-IV GVHD, Ⅲ-Ⅳ GVHD, transplant-related mortality and graft failure rate between PBSCT and BMT. This is a provisional file, not the final typeset article Conclusion: Before 2010, PBSCT was not superior to BMT in terms of 5-year OS, transplant-related mortality and graft failure rate, but it exhibited a higher risk of both chronic and acute GVHD. After 2010, PBSCT and BMT showed similar 3-year OS, GVHD risks, transplant-related mortality and graft failure rate. PB grafts are more suitable for HSCT of the AA for convenience and pain relief.